Migrasomes: key players in immune regulation and promising medical applications - Li, Shuping; Zhou, Yanjie; Hu, Tingting; Li, Mei; Luo, Yao; Chen, Jie (Frontiers in Immunology, 2025)
Migrasomes are newly discovered extracellular organelles released by migrating cells, such as immune cells, tumor cells, and other special functional cells like podocytes and embryonic cells. They contain a diverse array of constituents, including proteins, lipids, and RNA which can be released to the designated location to activate surrounding cells, thereby facilitating intercellular communication and signal transduction. Since then, our understanding of the mechanism and function of the migrasomes has expanded exponentially, with recent evidence indicating they are involved in various physiological and pathological processes, particularly in immune regulation. Furthermore, methods and techniques for extracting, detecting, and characterizing migrasomes are constantly advancing. Herein, we summarize the current understanding of migrasomes and their key roles in modulating immune responses, as well as the prospective challenges surrounding their clinical application, aiming to provide novel insights into the emerging organelles.